Synthesis, Characterization, 81Br NMR and Electronic Spectra of [(C4H9)4N][CrO3Br] and [(C4H9)4N][FeCl3Br] - KOHESTANI, BEHNAM; GHAMMAMY, SHAHRIARE; DASTPEYMAN, SAMANEH; POURAMINI, MOSTAFA; MALEKFAR, RASOUL; GHOLAMIAN, FOROZAN; JAVANSHIR, ZAHRA; RAFIE, SHAHNAZ (Asian Journal of Chemistry, 2010)
Two new ionic complexes of transition metals with tetrabutylammonium cation were synthesized. One of them is tetrabutylammonium bromotrioxochromate(VI), (C4H9)4N [CrO3Br] (TBABC), that easily synthesized in a nearly quantitative yield using a direct reaction of Cr(VI) oxide and tetrabutylammonium bromide. Another is tetyrabutylammonium bromotrichloroferrate(III), [(C4H9)4N][FeCl3Br], (TBABF), that has been synthesized by reaction of tetrabutylammonium bromide with FeCl3 salt. These compounds were characterized by IR, UV/Visible, 81Br NMR, 13C NMR and 1H NMR techniques. The electronic and vibrational spectra of TBABC and TBABF have been measured and studied. In TBABC the intervening band has been identified with oxygen-to-chromium charge transfer. This band exhibits a partially resolved vibrational progression or vibronic coupling due to excitation of a symmetric stretching mode in the CrO3 group.